2011
DOI: 10.1002/gps.2694
|View full text |Cite
|
Sign up to set email alerts
|

Personalised caregiver support: effectiveness of psychosocial interventions in subgroups of caregivers of people with dementia

Abstract: This study gives a first overview of successful psychosocial interventions in subgroups of caregivers of people with dementia. It makes clear that until now, relatively little research has been done into subgroups of these caregivers. It also suggests that more research is needed to better understand which psychosocial interventions are effective for specific subgroups of caregivers of people with dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
66
2
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 39 publications
3
66
2
2
Order By: Relevance
“…[73][74][75][76][77][78][79][80][81] Six of these focused on carers of people with dementia, [73][74][75][76][77][78] two focused on carers of people with mental health problems 79,80 and one focused on carers of people with multiple conditions. 81 In terms of types of interventions and outcomes, the literature appeared broadly similar to that covered in medium-and high-quality reviews.…”
Section: Overview Of the Medium-quality Reviewsmentioning
confidence: 99%
“…[73][74][75][76][77][78][79][80][81] Six of these focused on carers of people with dementia, [73][74][75][76][77][78] two focused on carers of people with mental health problems 79,80 and one focused on carers of people with multiple conditions. 81 In terms of types of interventions and outcomes, the literature appeared broadly similar to that covered in medium-and high-quality reviews.…”
Section: Overview Of the Medium-quality Reviewsmentioning
confidence: 99%
“…Most people with dementia live at home and are cared for by informal caregivers, mostly spouses and children, who play a crucial role in the supervision and therapy because of the progressive mental decline of the disease. Knowing that on the one hand there is a high cost of the disease for the society due to frequent hospitalization and permanent institutionalization in nursing homes and, on the other hand, people with dementia prefer to remain in their trusted environment as long as possible, it can be stated that informal caregivers are probably cost saving for society, but also essential in the care process [1][2][3][4][5][6][7][8][9]. Especially given the emerging focus on person-centered care, caregivers are indispensable to maximize well-being of people with dementia since they are best placed to identify their unique needs and desires [10].…”
Section: Introductionmentioning
confidence: 99%
“…Most research in the past decade has shown that informal caregivers have more health problems, visit healthcare professionals more frequently, suffer from isolation, and have an increased risk of depression, distress, and other illness [1,2,6,[11][12][13][14][15]. Because caregiver burden can reduce quality of caregiving and increases the likelihood of care-recipient placement into institutional care, there is also a substantial risk for the care-recipient [6,16,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reviews and meta-analyses noted the effects of interventions in caregiver's psychological well-being (Pinquart & Sorensen, 2006;Selwood, Johnston, Katona, Lyketsos, & Livingston, 2007;Thompson et al, 2007;Van Mierlo, Meiland, Van der Roest, & Droes, 2012). Among the different types of interventions, those providing psychoeducation coupled with an active participation of caregivers within a cognitive-behavioural therapy (CBT) framework are considered to be the most effective in reducing burden and increasing general well-being (Losada Baltar, Izal Fernandez de Troconiz, Montorio Cerrato, Marquez Gonzalez, & Perez Rojo, 2004;Pinquart & Sorensen, 2006;Selwood et al, 2007;Thompson et al, 2007).…”
Section: Introductionmentioning
confidence: 99%